2009
DOI: 10.5293/ijfms.2009.2.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Study on Design of Air-water Two-phase Flow Centrifugal Pump Based on Similarity Law

Abstract: A conventional centrifugal pump causes a drastic deterioration of air-water two-phase flow performances even at an air-water two-phase flow condition of inlet void fraction less than 10% in the range of relatively low water flow rate. Then we have developed a two-phase flow centrifugal pump which consists of a tandem arrangement of double rotating cascades and blades of outer cascade have higher outlet angle more than 90º. In design of the two-phase flow pump for various sized and operating conditions, similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Other contributions, like Schäfer et al [15] and Neunann et al [16], performed investigations using gamma-ray tomography techniques to find local discontinuities in pump characteristics. Furukawa et al [17] and Matushita et al [18] tested flow visualizations on a specific pump design with a tandem blade impeller set-up. Among them, most of the tested pump models used two-dimensional blade shapes transparent shroud impellers and paid little attention to the rotor-stator interaction (RSI) area.…”
Section: Introductionmentioning
confidence: 99%
“…Other contributions, like Schäfer et al [15] and Neunann et al [16], performed investigations using gamma-ray tomography techniques to find local discontinuities in pump characteristics. Furukawa et al [17] and Matushita et al [18] tested flow visualizations on a specific pump design with a tandem blade impeller set-up. Among them, most of the tested pump models used two-dimensional blade shapes transparent shroud impellers and paid little attention to the rotor-stator interaction (RSI) area.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the axial flow pump model, which consists of four IGVs, four impellers, and seven DVs. Applying the similarity law [10][11][12][13][14][15], the actual model is scaled down eight times to save time and computer resources. Some main parameters of the pump model are shown in table 1.…”
Section: Axial-flow Pump Modelmentioning
confidence: 99%
“…Successful impeller and vane diffuser specific sets of designs are achieved by the same research group (Furukawa et al [32,33]). Some extensions are also proposed by Matsushita et al ([34,35]) looking at possible application of similarity laws for such designs. They all presented interesting studies, developing different kind of tandem arrangement cascades and blades as shown in Figure 12.…”
Section: Particular Impeller Pump Designsmentioning
confidence: 99%